Magnetic iron oxide nanoparticle-loaded hydrogels for photothermal therapy of cancer cells - Ji, Yunfei; Wang, Chunpu (Frontiers in Bioengineering and Biotechnology, 2023)
Non-invasive photothermal therapy (PTT) is a competitive treatment for solid tumors, while the efficacy is largely dependent on the effective retention of photothermal converters in tumor tissues. Herein, the development of iron oxide (Fe3O4) nanoparticle-loaded alginate (ALG) hydrogel platform for PTT of colorectal cancer cells is reported. Fe3O4 nanoparticles synthesized via coprecipitation method after reaction of 30 min have a small size (61.3 nm) and more suitable surface potential, and can mediate PTT under near-infrared (NIR) laser irradiation. The premix of Fe3O4 nanoparticles and ALG hydrogel precursors can be gelatinized by Ca2+-mediated cross-linking to form this therapeutic hydrogel platform. The formed Fe3O4 nanoparticles can be effectively taken up by CT26 cancer cells and induce the death of CT26 cells in vitro under NIR laser irradiation because of their excellent photothermal property. In addition, Fe3O4 nanoparticle-loaded ALG hydrogels show negligible cytotoxicity at the studied concentration range, but can significantly kill cancer cells after PTT effect. This ALG-based hydrogel platform provides a valuable reference for subsequent in vivo studies and other related studies on Fe3O4 nanoparticle-loaded hydrogels.